Results of a multicentre UK‐wide retrospective study evaluating the efficacy of brentuximab vedotin in relapsed, refractory classical Hodgkin lymphoma in the transplant naive setting. (31st August 2017) - Eyre, Toby A.; Phillips, Elizabeth H.; Linton, Kim M.; Arumainathan, Arvind; Kassam, Shireen; Gibb, Adam; Allibone, Suzanne; Radford, John; Peggs, Karl; Burton, Cathy; Stewart, Gillian; LeDieu, Rifca; et al.
Summary: Relapsed or refractory classical Hodgkin lymphoma (cHL) is associated with a poor outcome when standard chemotherapy fails. Brentuximab vedotin (BV) is an anti‐CD30 monoclonal antibody‐drug conjugate licensed for use at relapse after autologous stem cell transplant (ASCT) or following two prior therapies in those unsuitable for ASCT. There are limited data assessing the ability of BV to enable curative SCT. We performed a UK‐wide retrospective study of 99 SCT‐naïve relapsed/refractory cHL. All had received 2 prior lines and were deemed fit for transplant but had an insufficient remission to proceed. The median age was 32 years. Most had nodular sclerosis subtype, Eastern Cooperative Oncology Group performance status 0–1 and advanced stage disease. The median progression‐free survival (PFS) was 5·6 months and median overall survival (OS) was 37·2 months. The overall response rate was 56% (29% complete response; 27% partial response). 61% reached SCT: 34% immediately post‐BV and 27% following an inadequate BV response but were salvaged and underwent deferred SCT. Patients consolidated with SCT had a superior PFS and OS to those not receiving SCT ( P  < 0·001). BV is an effective, non‐toxic bridge to immediate SCT in 34% and deferred SCT in 27%. 39% never reached SCT with a PFS of 3·0 months, demonstrating the unmet need to improve outcomes in those unsuitable for SCT post‐BV.